Color Atlas of Zebrafish Histology and Cytology - Lin, Jinxing; Chen, Qiusheng; Hu, Jianhua (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book elucidates the tissue structure and cell composition of the organs of zebrafish at the microscopic, ultrastructural and molecular levels. The distribution of important macromolecular substances is shown and the morphological relationship between different components is analyzed. The book is divided into 15 chapters and contains more than 700 structural photos, all of which are original experimental pictures of the research group. It shows the histological panorama of the whole zebrafish both in cross and longitudinal sections and covers and interprets the tissues and organs of zebrafish in detail, including oropharynx, taste buds, pharyngeal teeth, liver, etc. A brief text description of the structure and function meaning is available for every picture to facilitate the audience understanding the theoretical knowledge more vivid and concrete. In addition, the 3D reconstruction of the main organs of zebrafish is completed by computer-aided technology, and the three-dimensional morphology of the organs is displayed in an intuitive form. This book provides a reference for postgraduates and researchers in anatomy, biology, animal medicine, animal science, aquaculture, developmental biology, medicine, and experimental animals.
Chapter 1. Whole Zebrafish Section Atlas -- Chapter 2. Digestive Tract -- Chapter 3. Digestive Gland -- Chapter 4. Respiratory System -- Chapter 5. Urinary Organs -- Chapter 6. Male Gonads -- Chapter 7. Female Gonads -- Chapter 8. Immune Organs -- Chapter 9. Endocrine Organs -- Chapter 10. Circulation and Blood -- Chapter 11. Skin, Scales and Fins -- Chapter 12. Nervous System -- Chapter 13. Sensory Organs -- Chapter 14. Muscles -- Chapter 15. Spine and Cartilage.
Keywords: Biology-Technique.; Anatomy, Comparative; Zoology; Experimental Organisms; Animal Anatomy; Zoology